2022
DOI: 10.48550/arxiv.2203.12794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning the Dynamics of Autonomous Linear Systems From Multiple Trajectories

Lei Xin,
George Chiu,
Shreyas Sundaram

Abstract: We consider the problem of learning the dynamics of autonomous linear systems (i.e., systems that are not affected by external control inputs) from observations of multiple trajectories of those systems, with finite sample guarantees. Existing results on learning rate and consistency of autonomous linear system identification rely on observations of steady state behaviors from a single long trajectory, and are not applicable to unstable systems. In contrast, we consider the scenario of learning system dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, their analysis discards all but the last state transition within a trajectory, reducing to iid learning over only m examples. Zheng and Li (2021); Xin et al (2022) study the recovery of Markov parameters from partially observed states over many trajectories. However, their error bounds do not decrease with longer training horizons T , since the number of Markov parameters one must recover scales with the trajectory length.…”
Section: Related Workmentioning
confidence: 99%
“…However, their analysis discards all but the last state transition within a trajectory, reducing to iid learning over only m examples. Zheng and Li (2021); Xin et al (2022) study the recovery of Markov parameters from partially observed states over many trajectories. However, their error bounds do not decrease with longer training horizons T , since the number of Markov parameters one must recover scales with the trajectory length.…”
Section: Related Workmentioning
confidence: 99%